Karl Polanyi and twenty-first century socialism - Block, Fred (openDemocracy, 2016)
Polanyi’s views were the exact opposite of his contemporary, Joseph Schumpeter, who famously defined democracy as giving people a choice over which elite group would rule over them.
Keywords: socialism

Karl Polanyi for President - Iber, Patrick; Konczal, Mike (Dissent Magazine, 2016)
Are you a Bernie Sanders supporter? Chances are you'll like Karl Polanyi, too. An explainer.
Keywords: Great Transformation, The (Book); SANDERS, Bernie

Polanyi In Our Times - Saval, Nikal (The Nation, 2016)
Keywords: Greek crisis; biography; blog